2021
DOI: 10.3390/ijerph19010449
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption and Metabolic Risks in Young University Students

Abstract: The purpose of this study was to analyze the association between components of the diet, metabolic risks, and the serum concentrations of adiponectin and interleukin-6 (IL-6). With prior informed consent, an analytical cross-sectional study was carried out with 72 students in their first year of university. The subjects had a mean age of 19.2 ± 1.0 years and body mass index of 23.38 ± 4.2, and they were mainly women (80.6%). Sociodemographic, anthropometric, and dietary data and metabolic risk factors were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…High alcohol intake has also been associated with obesity in other studies, including university students [ 63 ] but not all [ 46 ]. The documented correlation of a high protein pattern with obesity is in line with the previously reported metabolic risks of this pattern [ 57 ]. Our results are of additive value given that a posteriori-defined unhealthy eating patterns are not usually associated with central obesity [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…High alcohol intake has also been associated with obesity in other studies, including university students [ 63 ] but not all [ 46 ]. The documented correlation of a high protein pattern with obesity is in line with the previously reported metabolic risks of this pattern [ 57 ]. Our results are of additive value given that a posteriori-defined unhealthy eating patterns are not usually associated with central obesity [ 60 ].…”
Section: Discussionsupporting
confidence: 86%
“…The median eggs and legumes intake (only for men) was in accordance with the recommendations [ 56 ]. A high meat intake has been reported in other studies in the same age group [ 57 ]. The low absolute intakes of several food groups may also be due to errors in estimating dietary intake, such as in the case of underreporting, which was high in our sample.…”
Section: Discussionsupporting
confidence: 75%
“…The acceptability and usefulness of the survey with tailored messages were equivalent to previous online tailored messaging programs in children alone in a school setting [ 32 ] and with their parents/caregivers in a clinical setting [ 31 ]. Liking of food items resembled dietary intakes observed in college adults, with higher liking of unhealthier food items suggesting higher intake of nutrient dense foods and risk of not meeting dietary guidelines [ 94 , 95 , 96 , 97 ]. Physical Activity was generally not liked with scores averaging between “It’s okay” and “like it”, suggesting that available activities or environment for these activities may be insufficient to be liked enough to compel physical activity behavior in college women [ 1 , 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 98%
“…As an illustration, countries in Asia, Europe, North America, and South America have reported an average Se intake of 2.6–48 µg/day, 10–60 µg/day, 80–221 µg/day, and 80–500 µg/day, respectively [ 31 ]. Although in Mexico it is still necessary to publish reliable information related to the Se content of the soil, it has been reported that there is an average Se intake of 37.6 ± 51.8 µg/day in the adult population, without differences between sexes [ 40 ]. Additionally, the adult population from northern Mexico has found that beans, corn tortillas and milk are responsible for 32%, 24%, and 19% of the daily Se intake, respectively [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in Mexico it is still necessary to publish reliable information related to the Se content of the soil, it has been reported that there is an average Se intake of 37.6 ± 51.8 µg/day in the adult population, without differences between sexes [ 40 ]. Additionally, the adult population from northern Mexico has found that beans, corn tortillas and milk are responsible for 32%, 24%, and 19% of the daily Se intake, respectively [ 40 , 41 ]. On the other hand, although ICP-MS is a reliable method widely used to quantify Se [ 42 , 43 ], and we carry out the Se measurement process with strict quality control, to date, there is no consensus regarding which biological sample is the most suitable for measuring Se status.…”
Section: Discussionmentioning
confidence: 99%